The Effect of Self-Efficacy and Entrepreneurial Mindset on Entrepreneurial Interests Student in Management Study Program Sembilanbelas November Kolaka University - Hendrik Hendrik; Almansyah Rundu Wonua; Muhammad Hasan (J-MAS (Jurnal Manajemen dan Sains), 2022)
To be able to reduce unemployment in educated students, one of the other options is entrepreneurship. Entrepreneurship can help reduce unemployment and make the younger generation aware and understand that they have alternatives in choosing their destiny by starting their own business and no need to keep looking and waiting to accept a job. This study aims to determine the effect of self-efficacy and entrepreneurial mindset on the entrepreneurial interest of students of the Management Study Program, Ninebelas November Kolaka University. The research method used in this research is quantitative, with questionnaires to answer the research problem formulation. The population in this study was 413 students of the USN Kolaka Management Study Program, with a sample of 203 people based on Slovin’s formula used. The analytical tool used was SPSS 23 to test the validity and reliability, while Partial Least Square (PLS) tests the research hypothesis model. The results of the analysis state that: 1) self-efficacy can increase interest in entrepreneurship; 2) an entrepreneurial mindset can increase interest in entrepreneurship.